Shelf life of lactic acid bacteria inoculated vacuum packed Tenualosa ilisha (Hamilton, 1822) at low temperature - Chowdhury, S.; Raychaudhuri, U.; Nath, S.; Dora, K. C. (Indian Journal of Fisheries, 2016)
Lactobacillus pentosus FPTLB13 was used as a biopreservative agent for hilsa steaks (Tenualosa ilisha) in vacuum packs at 5OC. The inoculated steaks (T) exhibited lowering of pH from 6.2 to 5.6 on day 12, probably due to production of organic acids. A sharp increase in total volatile base nitrogen was seen after day 12 of storage in treated steaks which could be attributed to extended lag phase of the spoilage microorganisms as result of competitive inhibition by lactic acid bacteria (LAB) and effect of acidification. Application of LAB cultures seems to have decreased the rate of trimethylamine formation (p<0.05) in the inoculated steaks at 5OC over a period of 15 days. Packing of hilsa steaks in vacuum cuts off oxygen supply and therefore lipid oxidation is reduced. The trend in changes in free fatty acid values of hilsa steaks suggested that application of LAB significantly reduced the values compared to control (C) (p<0.05). Application of LAB do not seem to improve (p>0.05) the texture and flavour of hilsa steaks, although the scores of overall acceptability suggests a significant improvement (p<0.05). The inoculated steaks were found to have a shelf life of 12 days under vacuum at 5OC.